(untitled) (El-Wahat Journal for Research and Studies, 2025)
Through this study, we aim to try to identify the reality of family relations in light of the use of social networking sites and the effects that this modern technology has had on the Algerian family, as we relied on the sample survey method, by applying the purposive sample to a sample of families in the city of Setif, which numbered ( 100) families, where the researchers designed the questionnaire tool as the main tool for collecting study data, and the results of the study revealed that the Algerian family depends on social networking sites as a tool for communication and entertainment. The study also showed that family relationships are damaged as a result of their frequent and intensive use of social networking sites. The study also concluded that The presence of coldness, emotional dryness, and lack of dialogue between members of the same family. Key words:Family, Famil Relations, Social Networking Sites